Role of Exosomal MicroRNAs and myomiRs in the Development of Cancer Cachexia-Associated Muscle Wasting - Marinho, Rodolfo; Alcântara, Paulo S. M.; Ottoch, José P.; Seelaender, Marilia (Frontiers in Nutrition, 2018)
Cachexia is a complex metabolic syndrome that promotes great weight loss, with marked muscle mass wasting. In the last years, many efforts have been directed to improve the understanding of the mechanisms involved in the disease. This syndrome is present in up to 80% of cancer patients and despite its clinical relevance, is underdiagnosed. The orchestration of the molecular and biochemical disruptions observed in cachexia are paralleled by inflammation and the communication among the different body compartments, including the tumor and the skeletal muscle, is still not completely described. One of the mechanisms that may be involved in the transduction of the inflammatory signals and the activation of catabolic status in muscle is the participation of exosomes containing microRNAs and muscle specific microRNAs (MyomiRs). Exosomes are nanovesicles, measuring from 30 to 100 μm, and able to carry microRNAs in the circulation, promoting cell-cell and tissue-tissue communication in an autocrine, paracrine and endocrine manner. MicroRNAs transported in exosomes are preserved from degradation, while these nanoparticles deliver the cargo to specific cell targets, making communication more efficient. Several microRNAs are known to modulate inflammatory pathways, to induce metastasis, to mediate cancer aggressiveness and even to participate in the regulation of protein synthesis and degradation pathways in the skeletal muscle. The aim of this mini-review is to describe the present knowledge about the role of exosomal microRNAs and myomiRs in the induction of muscle mass wasting in cancer cachexia state and to explain which transcription factors, proteins and pathways are regulated by these molecules.